Epistemic Semantics in Guarded String Models - Eric H Campbell; Mats Rooth (2021)
Constructive and computable multi-agent epistemic possible worlds models are interpreted as sets of guarded string models in an epistemic extension of Kleene Algebra with Tests (KAT